Telogen Effluvium and Alopecia Areata as Clinical Manifestations of Covid-19 - Medina, Laura Camila Garcia; Bertel, Fredys Daniel Chávez; Banegas, Adriana María Echeverría de; cuello, Dalila Rosa Fernández; Duarte, Karem Melissa Palomino; Montes, Yalisa Consuegra; Suárez, Viviana Yaneth Martínez; Parra, Didier Leonidas Diaz (Jour Med Resh and Health Sci, 2022)
Every day we naturally lose an average of 100 hairs, but different health problems can accelerate this loss, one of them is the current pandemic called by the World Health Organization as "Novel Coronavirus Disease 2019 (SARS-2 /COVID-19), where various predominantly respiratory clinical symptoms have been exposed such as fever, cough, chest pain, dyspnea, myalgia, asthenia and others that limit them to carry out their daily activities, however as the Over time, it has been shown to attack other organs, giving rise to new symptoms, although with less effect, such as severe hair loss, which have a negative impact on the quality of life of patients, favoring states of anxiety or depression as a result of what is known as effluvium. telogen or alopecia areata.